The View of Positive and Islamic Law Against Uploader Copyright - Wahyudi, Fachri; Hanifannur, Muhammad (Pemuliaan Hukum, 2023)
YouTube is a platform that is included in the protected cinematographic copyright. In this era of technology and creative industries, there are many people who commit criminal acts of video piracy on the YouTube platform and even broadcast without permission and get benefits. But for the creator, it is very detrimental. The subject matter studied in this research is about how copyright protection for YouTube uploaders in Article 40 of Law Number 28 of 2014 concerning Copyright and the perspective of Islamic law on copyright protection for YouTube uploaders. This research is a normative legal research using legislative and normative Islamic approaches. The results showed that copyright protection of YouTube uploaders is regulated in Law Number 28 of 2014 concerning Copyright which is technically regulated in Article 40 paragraph (1) letter m, although not specifically mentioned in the article but there are similarities in audiovisual form. When viewed in Islamic law, the act of YouTube re-uploader is included in jarimah ta'zir whose punishment is given to Ulil Amri (government).YouTube merupakan platform yang termasuk dalam hak cipta sinematografi yang dilindungi. Di era teknologi dan industri kreatif ini, banyak sekali oknum-oknum yang melakukan tindakan kriminal pembajakan video di platform YouTube bahkan menyiarkannya tanpa izin dan mendapatkan keuntungan. Namun bagi pencipta, hal tersebut sangat merugikan. Pokok permasalahan yang dikaji dalam penelitian ini adalah mengenai bagaimana perlindungan hak cipta bagi pengunggah YouTube dalam Pasal 40 Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta dan perspektif hukum Islam terhadap perlindungan hak cipta bagi pengunggah YouTube. Penelitian ini merupakan penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan dan pendekatan normatif Islam. Hasil penelitian menunjukkan bahwa perlindungan hak cipta terhadap pengunggah YouTube diatur dalam Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta yang secara teknis diatur dalam Pasal 40 ayat (1) huruf m, meskipun tidak disebutkan secara spesifik dalam pasal tersebut namun terdapat kesamaan dalam bentuk audiovisual. Jika ditinjau dalam hukum Islam, perbuatan pengunggah ulang YouTube termasuk dalam jarimah ta'zir yang hukumannya diserahkan kepada Ulil Amri (pemerintah).